Factors That Influence Termination Of Employment In Several Industrial Companies In Indonesia - Yolanda, Cindy (Jurnal Multidisiplin Sahombu, 2025)
The number of unemployed people in 2015-2024 tends to increase due to the emergence of layoffs influenced by the turmoil of economic growth which tends to stagnate or slightly decline, although inflation can be low, but the fluctuating Rupiah exchange rate weakens, and the value of imports tends to increase the price of goods needed for production makes the conditions of operational financing and production costs increasingly large and makes companies tend to reduce salary costs which have an impact on layoffs which give rise to an increase in open unemployment in Indonesia which is a burden on the State. This study aims to determine and analyze the extent to which economic growth, inflation, exchange rates, and import values ​​will affect the unemployment rate in Indonesia through the real impact of mass layoffs that will occur in 2024. The research method uses a quantitative descriptive method with data collection techniques using observation, questionnaires and literature studies, while data analysis uses classical assumption tests, multiple linear regression tests and hypothesis tests. Based on the research results, it can be concluded that information systems can become more relevant through the digital transformation process by analyzing organizational needs, modernizing technology infrastructure, digitizing business processes, integrating new technologies, building integration between systems and implementing monitoring and analytics, and it can be concluded that digital information systems can improve business operational efficiency by automating operational processes, integrating data and systems, making faster and more accurate decisions, reducing operational costs and facilitating overall digital transformation.